Parental Mediation to Reduce Device Addiction in Children with Emotional Disorders: A Case Study - Andan Firmansyah; Julia Putri (Inspirasi Foundation, 2024)
Objective: This case study aims to provide direct nursing care to children experiencing emotional disturbances due to gadget addiction through parental mediation in the city of Banjar. Method: The research methodology employed in this study is descriptive analysis, utilizing a case study approach to provide an objective assessment of the client's condition. The study focused solely on one subject, Patient An. R, who experienced emotional issues stemming from gadget addiction in Banjar City. The initial day involved conducting an assessment to determine the extent of gadget addiction and the client's emotional disturbances, educating the family on parental mediation techniques, and conducting a physical examination, which revealed no issues. Subsequent days involved monitoring changes in the client's device use intensity and emotional state. The final day assessed the effectiveness of the parental mediation intervention implemented by the family through data collection methods including interviews, observation, physical examinations, and documentation reviews. Results: The findings from the case study review phase indicated that the client exhibited emotional disturbances due to gadget addiction. The intervention utilized to reduce gadget addiction involved parental mediation, employing parental strategies to monitor device usage. Over a 3-day period, the child was encouraged to reduce daily device use duration, resulting in a successful reduction from 3-5 hours per day to 1-2 hours per day. Conclusion: Following the 3-day parental mediation intervention from June 18–20, 2023, the client's device use intensity aligned with the desired outcomes. Positive changes observed included decreased behavior of ignoring family members, enhanced communication among family members, and a reduction in aggressive behavior. Evaluation results indicated the resolution of one nursing diagnosis as planned. Despite the client's emotional disorder due to gadget addiction, the intervention had a positive impact, significantly reducing device usage from 3-5 hours to 1-2 hours per day.